Pengaruh Konflik Peran, Ketidakjelasan Peran, dan Kelebihan Peran terhadap Kepuasan Kerja dan Kinerja Auditor (Penelitian pada Kantor Akuntan Publik yang Bermitra Dengan Kantor Akuntan Publik Big Four di Wilayah DKI Jakarta) - Lidya Agustina (Universitas Kristen Maranatha, 2009)
The purpose of this research is to analyze and examine the hypothesis The Effect of Role Conflict, Role Ambiguity, and Role Overload on Job Satisfaction & Performance of junior auditor who work at Public Accountant Firm that has cooperation with big four Public Accountant Firms in DKI Jakarta simultaneously or partiality. This research performed at 93 junior auditors who work in between one until three years at public accountant firm that has cooperation with big four public accounting firms in DKI Jakarta at 2008. The research method that used in this research is descriptive analysis. Sampling technique employed in this research is by using simple random sampling. The time of research is cross-sectional. This research also using path analysis to analyze datas. The result of this research shows that Role Conflict, Role Ambiguity, and Role Overload both simultaneously and partiality give effects to job satisfaction and performance of junior auditor who work at public accountant firm that has cooperation with big four public accountant firms in DKI Jakarta. Keywords: Role Conflict, Role Ambiguity, Role Overload, Job Satisfaction, Auditor Job Performance